Capturing the early-age physicochemical transformations of alkali-activated fly ash and slag using ultrasonic pulse velocity technique. (July 2022) - Mahmood, Aziz Hasan; Babaee, Mahdi; Foster, Stephen J.; Castel, Arnaud
Abstract: Research has shown that reaction kinetics and physical transformation during alkali-activation of aluminosilicate materials are sensitive to both the compositions of raw precursors and the alkaline solution. Methods that allow for early observations relating to reaction kinetics, and that capture early-age physicochemical transformations with sufficient accuracy, can assist design engineers in bringing this new generation of binders to market. In this study, reaction heat and ultrasonic pulse velocity (UPV) evolutions of low calcium fly ash activated with alkaline solutions of different concentrations, and substituted with various dosages of ground granulated blast furnace slag (GGBFS), were systematically monitored using isothermal calorimetric and portable ultrasonic testing facilities. The incorporation of slag in a fly ash-based system influences the reaction kinetics, rate of physical transformation and morphological features. The study shows that UPV can capture the effect of slag addition on the microstructure densification, which is confirmed by measurements of heat evolution and SEM-EDS microstructural observations. A linear correlation of UPV was identified with the heat evolved. It was further shown that UPV tests can successfully capture workable time of alkali-activated fly ash paste blends that contain at least 10% of slag, noting that mixtures without any slag did not set within the first 24 h of activation. Further, improved dissolution of species, leading to an increased heat evolution, was observed with increasing activator alkalinity. SEM-EDS microstructural characterisation reveals an advanced dissolution of particles in a more alkaline environment, while higher silicate content leads to a more homogeneous morphology. The findings of this research will assist in the utilisation of alkali-activated materials in construction practice.